2021
DOI: 10.25308/aduziraat.867541
|View full text |Cite
|
Sign up to set email alerts
|

Düzenleyici Ekosistem Hizmetlerinden Hava Kalitesinin Efeler -Aydın Örneğinde İncelenmesi

Abstract: Bu çalışmanın amacı, Aydın ilinin en yoğun yapılaşmanın olduğu Efeler ilçesinde ağaç ve boylu çalıların oluşturduğu bitki taç örtüsünün hava kalitesinin iyileştirilmesi açısından düzenleyici ekosistem hizmetlerine katkısı ve Efeler ilçesindeki bu katkıların ekonomik tahmininin değerlendirilmesidir. Çalışmada bu ölçümler için i-Tree canopy v7.0 uygulaması kullanılmıştır. Çalışmada, Aydın İli Efeler ilçesinin 6 merkez mahallesinde 7 arazi örtüsü tipi ve dağılımları belirlenerek, her bir sınıf için rastgele topla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Yaşlı et al (2023) stated that there is concrete evidence that trees, urban green spaces and wider green infrastructure can provide significant reductions in urban temperatures and prevent health problems caused by heat waves. Many studies emphasize the role of tall shrubs, urban trees and urban forests in reducing carbon emissions, carbon capture and storage in urban areas (Goodale et al, 2002;Ersoy Tonyaloğlu et al, 2021;Öztekin Kara, 2022).…”
Section: Impact Of Air Pollutantmentioning
confidence: 99%
“…Yaşlı et al (2023) stated that there is concrete evidence that trees, urban green spaces and wider green infrastructure can provide significant reductions in urban temperatures and prevent health problems caused by heat waves. Many studies emphasize the role of tall shrubs, urban trees and urban forests in reducing carbon emissions, carbon capture and storage in urban areas (Goodale et al, 2002;Ersoy Tonyaloğlu et al, 2021;Öztekin Kara, 2022).…”
Section: Impact Of Air Pollutantmentioning
confidence: 99%
“…Arslan (2021) defined 1500 points for a study conducted on an area of 1643 ha in Çorum. Tonyaloğlu et al (2021) defined 6500 points for their study conducted on an area of 233.47 ha in Aydın. Hepcan & Hepcan (2017) defined 3000 points for their study conducted on an area of 54.47 ha in İzmir.…”
Section: I-tree Canopy Toolmentioning
confidence: 99%
“…In our study, the amount of O3 removed from the air was found to be 3.798.45 kg. This value was calculated as 1,821.60 kg in the study carried out in 6 neighborhoods of 233.47 ha in Aydın (Tonyaloğlu et al, 2021), 7,801.47 kg in Bahçelievler Neighborhood in Çorum (Arslan, 2021), and 1540 kg in the study carried out in an 80 ha urban area in Portugal Park (or Taquaral Lake) in Brazil (Olivatto, 2019). When proportioned in terms of area, this value we calculated for Kuzguncuk was found to be above the values for other study areas.…”
Section: Land Cover Types Identified In the Research Areamentioning
confidence: 99%